Предмет:
МатематикаАвтор:
аноним1) (3n + 3-n) / (9n + 1).
Упростим числитель:
3n + 3-n = 3n + 1 /3n = (3n * 3n + 1) / 3n = (9n + 1) / 3n.
Получим дробь:
(3n + 3-n) / (9n + 1) = (9n + 1) / (3n * (9n + 1)) = 1 / 3n = 3-n.
2) (5n + 1 – 5n) / 4.
Вынесем общий множитель за скобки:
(5n + 1 – 5n) / 4 = 5n (5 – 1) / 4 = 4 * 5n / 4 = 5n.
3) (4n + 4n + 1)2 / 42n – 2.
Упростим числитель:
вынесем общий множитель за скобки:
(4n + 4n + 1)2 = (4n (1 + 4))2 = 52 * 42n = 25 * 42n.
Упростим знаменатель:
42n – 2 = 42n / 42 = 42n / 16.
Получим дробь:
(4n + 4n + 1)2 / 42n – 2 = (25 * 42n) / (42n / 16) = 25 * 16 * 42n / 42n = 25 * 16 = 400.
Автор:
quincyДобавить свой ответ
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть